MEWFM 2021
DOI: 10.5742/mewfm.2021.93984
|View full text |Cite
|
Sign up to set email alerts
|

Use of eye drops self-medication in Aseer region, Southern Saudi Arabia

Abstract: Background: Self-medication is defined as the use of drugs to manage a self-diagnosed disease or complaint, or the intermittent or continued use of a prescribed drug for chronic or recurrent disease or symptoms. Self-medication includes getting medications without a prescription, resubmitting old prescriptions to buy medicines, sharing medicines with relatives or members of one’s social circle, or using leftover medicines stored at home. Risks are related to many factors including not only the possible severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Factor 1 contains items from the three theoretical dimensions of the RSM construct; In this factor, the Theory of Planned Behavior is anchored, in a more preponderant way, with the subjective norm construct, which is the belief about the social pressure exerted on an individual to perform or not perform a certain behavior and a person’s motivation to agree with this pressure ( 35 ) . This pressure from third parties involves people who influence the decision, motivation and practice of self-medication, such as family members ( 36 - 37 ) and friends ( 5 , 38 - 39 ) . This is reinforced by the fact that a study based on the Theory of Planned Behavior showed that 69% of spouses or friends influenced the taking of medications without prescriptions ( 5 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor 1 contains items from the three theoretical dimensions of the RSM construct; In this factor, the Theory of Planned Behavior is anchored, in a more preponderant way, with the subjective norm construct, which is the belief about the social pressure exerted on an individual to perform or not perform a certain behavior and a person’s motivation to agree with this pressure ( 35 ) . This pressure from third parties involves people who influence the decision, motivation and practice of self-medication, such as family members ( 36 - 37 ) and friends ( 5 , 38 - 39 ) . This is reinforced by the fact that a study based on the Theory of Planned Behavior showed that 69% of spouses or friends influenced the taking of medications without prescriptions ( 5 ) .…”
Section: Discussionmentioning
confidence: 99%
“…O fator 1 contém os itens das três dimensões teórica do construto AR; nesse fator, ancora-se, de modo mais preponderante, a Teoria do Comportamento Planejado, com o construto norma subjetiva, que é a crença acerca da pressão social exercida sobre um indivíduo para realizar ou não determinado comportamento e da motivação da pessoa em concordar com essa referida pressão ( 35 ) . Essa pressão de terceiros encontra pessoas que apresentam influências na decisão, motivação e prática da automedicação, como familiares ( 36 - 37 ) e amigos ( 5 , 38 - 39 ) . Reforça-se a isso que estudo com base na Teoria do Comportamento Planejado evidenciou que 69% de esposos ou amigos influenciaram a tomada de medicamentos sem receitas ( 5 ) .…”
Section: Discussionunclassified